UPAYA GURU MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PROSES PEMBELAJARAN SOSIOLOGI SMA SANTO FRANSISKUS ASISI - Yuliana, Yuliana; Bahari, Yohanes; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The Teacher's Efforts to Improve Student Learning Motivation in the Sociology Learning Process of Class XI IPS 1 of Santo Fransiskus Asisi High School Pontianak". The purpose of the study was to describe (1) the efforts of teachers to increase intrinsic motivation in the process of learning sociology in class XI IPS 1 Santo Fransiskus Asisi High School Pontianak. (2) The teacher's efforts to increase extrinsic motivation in the process of learning sociology in class XI IPS 1 of Santo Fransiskus Asisi High School Pontianak. The method used is a qualitative method with descriptive analysis. Data collection tools use observation guidelines, interview guidelines and documentation. The results of the study showed that (1) The efforts made by the teacher to increase the intrinsic motivation of students 'learning were paying attention to students' attitudes, giving motivation to students, maintaining the concentration of student learning, giving praise and recognition to successful students so that students had stronger self-confidence. (2) Efforts made by the teacher to improve extrinsic motivation of student learning, namely, the teacher guides and fosters students in learning, teachers utilize school facilities and infrastructure, teachers admonish and give advice to students who do not pay attention to learning activities and separate students' seats when chatting Teachers deliver learning material to create conducive social conditions for students in the classroom.Keywords: Teacher's Efforts, Intrinsic Motivation, Extrinsic Motivation